1994
DOI: 10.1128/jvi.68.6.3667-3673.1994
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis: a mechanism of cell killing by influenza A and B viruses

Abstract: In previous studies, we observed that the virulent avian influenza A virus A/Turkey/Ontario/7732/66 (Ty/Ont) induced severe lymphoid depletion in vivo and rapidly killed an avian lymphocyte cell line (RP9) in vitro. In examining the mechanism of cell killing by this virus, we found that Ty/Ont induced fragmentation of the RP9 cellular DNA into a 200-bp ladder and caused ultrastructural changes characteristic of apoptotic cell death by 5 h after infection. We next determined that the ability to induce apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(181 citation statements)
references
References 32 publications
10
168
2
1
Order By: Relevance
“…Other possible explanations for the different outcomes of MHV-3 infection of BALB/c and A/J macrophages might be variations in the levels of bcl-2, TNF-␣ or other cytokines important in decreasing programmed cell death in infected cells. In this regard, it was recently shown that overexpression of bcl-2 can block or delay apoptosis induced by Sindbis virus (Levine et al, 1996), La Crosse virus (Pekosz et al, 1996), adenovirus (Chiou et al, 1994), and influenza virus (Hinshaw et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Other possible explanations for the different outcomes of MHV-3 infection of BALB/c and A/J macrophages might be variations in the levels of bcl-2, TNF-␣ or other cytokines important in decreasing programmed cell death in infected cells. In this regard, it was recently shown that overexpression of bcl-2 can block or delay apoptosis induced by Sindbis virus (Levine et al, 1996), La Crosse virus (Pekosz et al, 1996), adenovirus (Chiou et al, 1994), and influenza virus (Hinshaw et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is closely related to a number of aspects of influenza A virus (IAV) infection. For instance, apoptosis plays a pivotal role in IAV elimination through the removal of the virus infected cells, and tissue damage during the course of IAV infection including multiple organ dysfunction is caused by apoptosis [1,2]. Further, abnormal induction of lymphocyte apoptosis is related in the disease symptoms of influenza, and apoptosis is also important to terminate inflammation through the induction of activation-induced cell death (AICD).…”
Section: Introductionmentioning
confidence: 99%
“…Infection by influenza A subtypes can occur through direct contact with an infected animal, exposure to contaminated environment, or ingestion of inadequately prepared food stuffs (7). Upon failure of host immunologic defenses (immunoglobulin A secretory antibody and mechanical respiratory mucociliary clearance), influenza viruses invade columnar respiratory epithelium, triggering a molecular cascade responsible for the inactivation of host-cell protein synthesis (9,13,14). Local destruction of respiratory epithelium, resulting in the release of pro-inflammatory cytokines, in addition to viral invasion of polymorphonuclear leukocytes, lymphocytes, and monocytes, are responsible for systemic symptoms (9,15).…”
Section: Discussionmentioning
confidence: 99%